Pengaruh Motivasi Belajar dan Mengajar di Era Modern - ema sahara ponorogo (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Learning and teaching motivation are two important components that are interraled and contribute significantly to the success of the educational process. This article aims to examine the influence of motivation from both students and teachers on the quality of education in the modern era. Using the latest literature and empirical research, this article reviews how intrinsic and extrinsic motivation can influence the learning process and academic outcomes, as well as how external factors such as technology and the school environment influence this motivation.